SIKAP PETANI TERHADAP PENGGUNAAN BENIH PADI (ORYZA SATIVA.L) BERSERTIFIKAT DI DESA AMBARKETAWANG KECAMATAN GAMPING KABUPATEN SLEMAN - Rahmawati, Mega (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2019)
The study aimed to know attitude of farmers with the usage of certified rice seeds (Oryza sativa. L). The study was conducted from February 7th to May31th, 2018 in Ambar Ketawang Village, Gamping District, Sleman Regency. The method used is the survey with the questionnaire instrument on the respondents determined by proportional random sampling on the members of farmer groups. Furthermore, the data are analysed statistically descriptive. The results showed that attitude of farmers with the usage of certified rice seeds (Oryza sativa. L) in the medium category because influenced by hesitant attitude caused by unproductive age, narrow land area, low economy condition and land ownership status only as cultivator.